2022
DOI: 10.1021/acs.joc.2c02297
|View full text |Cite
|
Sign up to set email alerts
|

DBU-Promoted Deaminative Thiolation of 1H-Benzo[d]imidazol-2-amines and Benzo[d]oxazol-2-amines

Abstract: A facile and efficient catalyst-/metal-/oxidant-free DBU-promoted deaminative thiolation reaction of 1H-benzo[d]imidazol-2-amines and benzo[d]oxazol-2-amines has been developed at room temperature conditions in a one-pot protocol. This practical three-component strategy represents a novel and environmentally friendly reaction pathway toward the straightforward synthesis of various 2-thio-1H-benzo[d]imidazoles and 2thiobenzo[d]oxazoles using carbon disulfide as a sulfur source through C−N bond cleavage and C−S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…After the polymeric characterization, some investigations were conducted to evaluate the material's behavior in contact with aqueous vapors and liquid organic phases, to verify the material's compatibility with possible final applications. 30–32…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the polymeric characterization, some investigations were conducted to evaluate the material's behavior in contact with aqueous vapors and liquid organic phases, to verify the material's compatibility with possible final applications. 30–32…”
Section: Resultsmentioning
confidence: 99%
“…After the polymeric characterization, some investigations were conducted to evaluate the material's behavior in contact with aqueous vapors and liquid organic phases, to verify the material's compatibility with possible final applications. [30][31][32] In this context, the thickness of the sensing material is crucial since very thin specimens have a faster response due to rapid diffusion processes, but low mechanical properties. 20 For this reason, a trade-off value of 0.5 mm was set (see ESI file and Fig.…”
Section: Papermentioning
confidence: 99%
“…For example, Yang and co-workers developed a copper-catalyzed domino synthesis of C-3 sulfenylated imidazo[1,2- a ]pyridine derivatives using carbon disulfide as a building block . In 2022, Guo and co-workers reported CS 2 as a convenient sulfur source for the synthesis of 2-thio-1 H -benzo[ d ]-imidazoles and 2-thiobenzo[ d ]oxazoles . Inspired by these elegant pioneering studies, we proposed a copper-catalyzed domino synthetic approach for the synthesis of β-hydroxysulfides via ring-opening coupling from styrene oxide, carbon disulfide, and iodobenzene.…”
Section: Introductionmentioning
confidence: 94%
“…15 In 2022, Guo and co-workers reported CS 2 as a convenient sulfur source for the synthesis of 2-thio-1H-benzo[d]-imidazoles and 2-thiobenzo[d]oxazoles. 16 Inspired by these elegant pioneering studies, we proposed a copper-catalyzed domino synthetic approach for the synthesis of β-hydroxysulfides via ringopening coupling from styrene oxide, carbon disulfide, and iodobenzene. Meanwhile, we also found that the corresponding (benzo[d]thiazol)-β-hydroxysulfide products can be obtained when using o-iodoaniline instead of iodobenzene (Scheme 1d).…”
Section: ■ Introductionmentioning
confidence: 99%